Examining the Reliability, Validity and Factor Structure of the DRS-15 with College Athletes - Leilani Madrigal; Diane L Gill; Kent M Eskridge (Psychological Topics, 2016)
Hardiness, comprising feelings of commitment, control and challenge, is most frequently measured with the Dispositional Resiliency Scale (DRS), but little work has been done with the brief 15-item version. To examine the factor structure, reliability, validity, and item functioning for gender invariance of the 15-item DRS with 525 collegiate athletes from a wide range of sports. Convergent and divergent validity were examined through relationships with mental toughness, grit and competitive anxiety. Participants completed measures of mental toughness, optimism, grit, competitive anxiety, and the DRS-15. Confirmatory Factor Analysis revealed a poor fit for the three-factor hardiness model, and subsequent exploratory factor analysis yielded a four-factor model with better fit than the three-factor structure. Additionally, several items appear to be biased towards males or females. The fourth factor may be unique to the collegiate athlete population, and related to perceived lack of control in future life directions. Convergent and divergent validity were supported through correlations of DRS scores with related measures. The four-factor model should be tested with different samples to determine if these changes should be adapted when using the DRS-15 in collegiate athletics or other settings.